2009
DOI: 10.1210/en.2008-1585
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Specific Effects of Nitric Oxide Deficiency on Parathyroid Hormone-Related Peptide (PTHrP) Responsiveness and PTH1 Receptor Expression in Cardiovascular Cells

Abstract: The missing influence of estrogen on endothelial nitric oxide (NO) synthase often forms the basis for a worsening of the cardiac risk profile for women in postmenopause. Various studies have shown that decreasing estrogen levels also directly effect the expression of PTHrP and TGFbeta1. PTHrP is involved in the endothelium-dependent regulation of coronary resistance and cardiac function. The current study investigates to what extent chronic NO deficit affects the cardiac effects of PTHrP. NO deficit was achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…The basis of differences in CVD risk has been attributed to declining levels of estrogens in women (2). In this issue, Schreckenberg et al (3) provide new insights into the mechanism of action of estrogens on heart tissue, showing that PTHrP is a crucial downstream mediator. The significance of their findings in the context of hormone replacement therapy (HRT) use is discussed below.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The basis of differences in CVD risk has been attributed to declining levels of estrogens in women (2). In this issue, Schreckenberg et al (3) provide new insights into the mechanism of action of estrogens on heart tissue, showing that PTHrP is a crucial downstream mediator. The significance of their findings in the context of hormone replacement therapy (HRT) use is discussed below.…”
mentioning
confidence: 99%
“…In noncardiac tissue, it is known that a deficiency of estradiol-17␤ decreases PTHrP expression (21). New research by Schreckenberg et al (3) in this issue of the journal has now demonstrated that this deficiency, manifested by a chronic lack of NO production, alters the response of the myocardium to PTHrP via TGF␤-correlated reduction in PTH receptor expression (3). Interestingly, in these studies, PTHrP was still able to induce vasodilatation in NO-deficient animals, suggesting that its mechanism of vasodilatation is independent of NO (3).…”
mentioning
confidence: 99%
“…L‐NAME treatment (30 mg/kg/day in tap water) has been used before to affect NO levels in rats 22. Captopril (30 mg/kg/day in tap water) or hydralazine (20 mg/kg/day in tap water) was administered as described 22, 23.…”
Section: Methodsmentioning
confidence: 99%
“…Captopril (30 mg/kg/day in tap water) or hydralazine (20 mg/kg/day in tap water) was administered as described 22, 23. L‐NAME was administered to rats for 2 weeks before either captopril or hydralazine were added with continuation of L‐NAME treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have indicated that PTH enhances myocardial contractility and improves cardiac function by influencing the shortening fraction and autorhythmicity (7,8). Additionally, PTH directly dilates the coronary artery and promotes myocardial microcirculation, thereby improving the myocardial oxygen supply and cardiac pump function (912). Furthermore, PTH regulates the secretion and expression of stromal derived factor 1, matrix metalloproteinase 9 and granulocyte colony stimulating factor in the bone marrow and induces the mobilization and homing of cluster of differentiation (CD)34/CD45-positive bone marrow stem cells, thereby promoting the release of vascular endothelial growth factor and angiogenesis (1316).…”
Section: Introductionmentioning
confidence: 99%